Vibration control of rotors mounted in hydrodynamic bearings lubricated with magnetically sensitive oil by changing their load capacity - Jaroslav Zapoměl; Petr Ferfecki (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
Rotors of rotating machines are often mounted in hydrodynamic bearings. Loading alternating between the idling and full load magnitudes leads to the rotor journal eccentricity variation in the bearing gap. To avoid taking undesirable operating regimes, its magnitude must be kept in a certain interval. This is offered by the hydrodynamic bearings lubricated with smart oils, the viscosity of which can be changed by the action of a magnetic field. A new design of a hydrodynamic bearing lubricated with magnetically sensitive composite fluid is presented in this paper. Generated in the electric coil, the magnetic flux passes through the bearing housing and the lubricant layer and then returns to the coil core. The action of the magnetic field on the lubricant affects the apparent fluid viscosity and thus the position of the rotor journal in the bearing gap. The developed mathematical model of the bearing is based on applying the Reynolds equation adapted for the case of lubricants exhibiting the yielding shear stress. The results of the performed simulations confirmed that the change of magnetic induction makes it possible to change the bearing load capacity and thus to keep the rotor journal eccentricity in the required range. The extent of control has its limitations. A high increase in the loading capacity can arrive at the rotor forced vibration’s loss of stability and induce large amplitude oscillation.